2014
DOI: 10.1111/tmi.12365
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the economic burden of illness for tuberculosis patients in Benin: determinants and consequences of catastrophic health expenditures and inequities

Abstract: Abstractobjectives To inform policy-making, we measured the risk, causes and consequences of catastrophic expenditures for tuberculosis and investigated potential inequities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
56
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 26 publications
13
56
4
Order By: Relevance
“…Similarly, we identified many studies in the recent period that determined catastrophic costs due to TB care (diagnosis and treatment), but did not provide data specifically for diagnosis [11,3336]. A systematic review from Africa (studies from 1990 to 2010) revealed that the pre-diagnostic costs for TB varied between 10.4 and 35% of pre-TB AHI [12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we identified many studies in the recent period that determined catastrophic costs due to TB care (diagnosis and treatment), but did not provide data specifically for diagnosis [11,3336]. A systematic review from Africa (studies from 1990 to 2010) revealed that the pre-diagnostic costs for TB varied between 10.4 and 35% of pre-TB AHI [12].…”
Section: Discussionmentioning
confidence: 99%
“…Both these studies estimated direct costs only without accounting for the indirect costs. Using a 10% of annual household income cutoff as threshold, 71.8% of the patients in Benin, West Africa experienced the catastrophic impact of TB [22]. With total costs ≥20% of household annual income, 39% Peruvian households incurred catastrophic costs [14].…”
Section: Discussionmentioning
confidence: 99%
“…In specific settings, certain dissaving variables may be more relevant to, and correspond more closely with, the likelihood of incurring catastrophic costs. For example, in rural sub-Saharan Africa where formal loans or payments may be less frequent, other dissaving variables such as selling livestock may be more important contributors to dissaving [2]. In addition, while there is scope for measuring dissaving elements longitudinally as a binary variable at different time points throughout TB treatment ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, catastrophic costs were defined financially as TB-related out-of-pocket expenses that led to worsening impoverishment of TB-affected households [24]. In recent research, we defined a clinically relevant catastrophic costs threshold, demonstrating that TB patients from households that incurred total TB-related household costs of ≥20% of their household annual income were more likely to die, or not complete, or not be cured by, TB treatment [5].…”
Section: Introductionmentioning
confidence: 99%